Exploration of Sleep as a Specific Risk Factor for Poor Metabolic and Mental Health: A UK Biobank Study of 84,404 Participants - Zhu G (Dove Medical Press, 2021)
Gewei Zhu,1 Sophie Cassidy,2 Hugo Hiden,3 Simon Woodman,3 Michael Trenell,4 David A Gunn,5 Michael Catt,6 Mark Birch-Machin,1,6 Kirstie N Anderson7 1Faculty of Medical Sciences, Translational and Clinical Research Institute, Newcastle University, Newcastle Upon Tyne, UK; 2Central Clinical School, Faculty of Medicine and Health, The University of Sydney, Sydney, NSW, Australia; 3National Innovation Centre for Data, School of Computing, The Catalyst, Newcastle Helix, Newcastle Upon Tyne, UK; 4NIHR Innovation Observatory, The Catalyst, Newcastle Helix, Newcastle upon Tyne, UK; 5Colworth Science Park, Sharnbrook, Bedfordshire, UK; 6National Innovation Centre for Ageing, The Catalyst, Newcastle Helix, Newcastle upon Tyne, UK; 7Department of Neurology, Royal Victoria Infirmary, Newcastle upon Tyne, UKCorrespondence: Kirstie N AndersonDepartment of Neurology, Royal Victoria Infirmary, Newcastle upon Tyne, UKTel +44 01912823833Email kirstieanderson@nhs.netPurpose: Short and long sleep durations have adverse effects on physical and mental health. However, most studies are based on self-reported sleep duration and health status. Therefore, this longitudinal study aims to investigate objectively measured sleep duration and subsequent primary health care records in older adults to investigate the impact of sleep duration and fragmentation on physical and mental health.Methods: Data on objective sleep duration were measured using accelerometry. Primary care health records were then obtained from the UK Biobank (n=84,404). Participants (mean age, 62.4 years) were divided into five groups according to their sleep duration derived from the accelerometry data: < 5 hours, 5– 6 hours, 6– 7 hours, 7– 8 hours and > 8 hours. ICD-10 codes were used for the analysis of primary care data. Wake after sleep onset, activity level during the least active 5 hours and episodes of movement during sleep were analysed as an indication for sleep fragmentation. Binary regression models were adjusted for age, gender and Townsend deprivation score.Results: A “U-shaped” relationship was found between sleep duration and diseases including diabetes, hypertension and heart disease and depression. Short and long sleep durations and fragmented sleep were associated with increased odds of disease.Conclusion: Six to eight hours of sleep, as well as less fragmented sleep, predicted better long-term metabolic and mental health.Keywords: sleep, health, UK Biobank, primary care